Virus-like particles of macrobrachium rosenbergii nodavirus capsid as a carrier for immunogenic components - Tan, Wen Siang; Ho, Kok Lian; Yong, Chean Yeah; Goh, Zee Hong; Omar, Abdul Rahman; Yeap, Swee Keong (2014)
The present invention provides recombinant plasmids comprising MrNV capsid gene and optionally also myc gene carrying immunogenic component (such as ‘a’ determinant of HBV and M2e of influenza virus genes) at the 3’ terminus of the MrNV capsid gene and/or 5’ terminus of myc and hexa-His coding region. The present invention further provides spherical epitope-displaying virus-like particles (VLPs) comprising the MrNV capsid protein and one or more immunogenic components, such as ‘a’ determinant of HBV and M2e of influenza virus. The particles may contain one or more copies of each epitope. The invention further provides a method of producing such VLPs, and uses of such VLPs.